Neurology of Critical Care - Wijdicks, Eelco F. M. (Seminars in Neurology, 2016)
It is a truism that care of the patient with an acutely severe neurologic illness starts with a full neurologic examination. Neurologic examination is followed by tests (neuroimaging and laboratory) resulting in a diagnosis (presumptive or definitive) and treatment (definitive or preemptive) and followed by admission for supportive care and more treatment. The sequence of decisions depends on the diagnosis, but treatment may be needed to diagnose a neurologic disorder. To find out what underlies the acute presentation of certain neurologic conditions requires (1) interpretation of neurologic findings, (2) interpretation of neuroimaging, (3) linking laboratory abnormalities to certain clinical neurologic findings, and (4) evaluation of improvement or refractoriness after treatment. Here the author reviews the lesion localization, the determination of cause and severity of coma, and the assessment of acute neuromuscular failure and spinal cord injury. There are clinical patterns of deterioration in each of these patients that should be known.
Keywords: examination; localization; brainstem reflexes; coma scales; deterioration